PEKERJA SEKTOR INFORMAL DI KOTA AMBON - BAKARBESSY, DEREK (JURNAL BADATI, 2019)
This study aims to find out informal sector workers in Ambon city through case study. Determination of stratified random samples by first making the population classification according to certain characteristics and after that determined the number of samples with randomly selected system of 211 people, consisting of: people, seller drinks 109 people, fruit vendors 41, meatball seller 45 people. The data were analyzed quantitatively, in order to find out the utilization rate of labor force in the informal sector under study, the approach of the "Labor Utilization Approach" theory was used. The informal sector, whether viewed from the perspective of income, working hours, or education, is in a state of "adequate utilization". The informal sector workers in carrying out their business have earned some of the income they use to support their families and continue their business. The informal sector in maintaining its existence faces various problems. A particularly prominent problem is the lack of capital, the place of business, and the marketing of results.